2016
DOI: 10.1007/5584_2016_73
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Human Herpesvirus 8 Infection in Diabetes Type 2 Patients and Detection of a New Virus Subtype

Abstract: The prevalence of Human Herpesvirus 8 (HHV8) DNA and antiviral antibodies in Diabetes type 2 (DM2) and control subjects was studied, in order to confirm a possible link between DM2 and HHV8 infection. The HHV8-DNA from diabetic patients was typed for detecting possible genomic differences with known HHV8 reference viruses.DM2 patients and healthy controls were examined for the presence of HHV8 DNA into the peripheral blood lymphocytes. Both anti-lytic and latent phase antibodies were detected in HHV8 positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…The results were also strengthened by the observation of increased antibody titers and viral DNA load in participants with higher blood glucose levels. These findings are generally in agreement with those of recent studies on KSHV infection among diabetic patients from European and African countries (Caselli et al, 2014;Ingianni et al, 2007;Piras et al, 2017;Sobngwi et al, 2008). In addition, it was found that ethnicity might be inversely associated with the level of antibody titers and viral load: the Uygur population had increased antibody titer levels, while the viral DNA load was higher in the Han population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results were also strengthened by the observation of increased antibody titers and viral DNA load in participants with higher blood glucose levels. These findings are generally in agreement with those of recent studies on KSHV infection among diabetic patients from European and African countries (Caselli et al, 2014;Ingianni et al, 2007;Piras et al, 2017;Sobngwi et al, 2008). In addition, it was found that ethnicity might be inversely associated with the level of antibody titers and viral load: the Uygur population had increased antibody titer levels, while the viral DNA load was higher in the Han population.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, diabetic patients are at higher risk of KS and other KSHV-associated tumors (Anderson et al, 2008;Chang et al, 2017). Although the study results conflict with those of a study by Piras et al (Piras et al, 2017), this observation is supported by other studies that have shown that high glucose levels can significantly increase lytic reactivation of KSHV. Multiple signaling pathways involved in the lifecycle of KSHV have been proven to be modulated by high glucose in various cell types (Chang et al, 2017;Ye et al, 2016).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…A possible association of HHV8 infection with type-2 diabetes has recently been proposed [16][17][18][19]. Insulin hyper-secretion and consumption is considered a possible initiating event of obesity and diabetes, and discovering the causes that induce insulin hypersecretion could help to find a solution for diabetes treatment [20].…”
Section: Resultsmentioning
confidence: 99%
“…The increased insulin-uptake induced an increase of glucose accumulation in HUVEC cells. Recently, Piras and colleagues investigated the prevalence of HHV8 DNA and specific antiviral antibodies in diabetes mellitus type 2 (DM2) patients and control subjects [18]. They reported the presence of anti-lytic and -latent antibodies in HHV8-positive DM2 subjects and in non-DM2 controls.…”
Section: Introductionmentioning
confidence: 99%